Non-coding RNAs in Natural Killer/T-Cell Lymphoma - Mei, Mei (Front Oncol, 2019)
Natural killer/T-cell lymphoma (NKTCL) is a rare and aggressive subtype of non-Hodgkin's lymphoma that is associated with a poor outcome. Non-coding RNAs (ncRNAs), which account for 98% of human RNAs, lack the function of encoding proteins but instead have the important function of regulating gene expression, including transcription, translation, RNA splicing, editing, and turnover. However, the roles and mechanisms of aberrantly expressed ncRNAs in NKTCL are not fully clear. Aberrant expressions of microRNA (miRNAs) affect the PI3K/AKT signaling pathways (miRNA-21, miRNA-155, miRNA-150, miRNA-142, miRNA-494), NF-κB (miRNA-146a, miRNA-155) and cell cycle signaling pathways to regulate cell function. Moreover, Epstein-Barr virus (EBV) encoded miRNAs and EBV oncoprotein LMP-1 regulated the expression of cellular genes that induce invasion, metastasis, cell cycle progression and cellular transformation. In addition, NKTCL-associated Long non-coding RNA (lncRNA) ZFAS1 regulated certain pathways and lncRNA MALAT1 acted as a predictive marker. This review article provides an overview of ncRNAs associated with NKTCL, summarizes the function of significantly differentially expressed hotspot non-coding RNAs that contribute to the pathogenesis, diagnoses, treatment and prognosis of NKTCL and discusses the relevance of these ncRNAs to clinical practice.